CRITLEVEL: An Exploratory Procedure for the Evaluation of Quantitative Prognostic Factors - Abel, U.; Berger, Jutta; Wiebelt, H. (Methods of Information in Medicine, 1984)
CRITLEVEL is a simple but efficient graphic tool for determining those levels of quantitative prognostic factors at which the most pronounced deterioration of prognosis takes place.
Keywords: Prognostic Factors; Critical Values; Failure Time Analysis